The relationship between body mass index in late pregnancy and fetomaternal blood flow parameters: A prospective cross-sectional study (Annals of Medical Research, 2021)
Aim: To evaluate a possible relationship between body mass index and fetomaternal blood flow parameters in women with term pregnancy.Material and Methods: This study was performed on pregnant women undergoing routine third trimester ultrasound scans. Women were divided into four groups [underweight ( 18.5 kg/m2), normal weight (18.5–24.9 kg/m2), overweight (25-29.9 kg/m2) and obese (≥30 kg/m2)]. The uterine artery (UtA), umbilical artery (UA) and middle cerebral artery (MCA) were examined using color Doppler according to the standard protocols. The systole/diastole (S/D) ratio, pulsatility index (PI), and resistance index (RI) values of UtA, UA and MCA were recorded.Results: All Doppler findings were found to be similar among normal weight, overweight and obese women. There was a positive correlation between UtA-RI and maternal BMI (r=0.350; p0.01). There was a positive association between both UA-PI and UA-RI values with maternal BMI (r=0.372; p0.01; r=0.289; p=0.001, respectively). Also, we observed a positive association between both MCA-RI and MCA-S/D values with maternal BMI (r=0.180; p=0.04; r=0.181; p=0.04, respectively). Conclusion: Normal weight, overweight and obese women with term pregnancy have similar maternal and fetal blood flow parameters. Obese women should be informed about the risks of obesity during pregnancy, and they should be supported to lose weight before conception.
Keywords: Body mass index; doppler ultrasonography; middle cerebral artery; obesity; umbilical artery; uterine artery